The Legal Status Of Interns In Algerian Employment Legislation - Bourayou Mohammed Yacine (Kurdish Studies, 2024)
This study aims to highlight the internship phase as a mandatory stage that every newly employed person goes through, by identifying the legal status of interns, which is characterized by its probabilistic and uncertain nature regarding their official appointment. An intern may be officially appointed in the designated position, thereby enjoying all the rights granted to any employee and legal protection against any dismissal issued by the administration, or they may be dismissed without any compensation or prior notice. The study reached several conclusions, the most important of which is that interns in Algerian employment legislation do not enjoy adequate legal protection compared to that of appointed employees.